Percutaneous Management of Benign and Postoperative Biliary Strictures - Shao, Haibo; Arellano, Ronald S (Digestive Disease Interventions, 2017)
Biliary strictures are an uncommon yet challenging clinical problem. They are often iatrogenic in nature, usually the consequence of hepatobiliary surgery. Although the etiology may be benign, the clinical consequences, if unrecognized, can progress to ascending cholangitis, sepsis, and hepatic abscesses. Optimal treatment requires expertise and input from multiple specialties, including gastroenterology, surgery, infectious disease, and interventional radiology. Currently, available interventional techniques play a critical role in the management of patients with benign biliary strictures.
Keywords: benign biliary stricture; percutaneous intervention; biliary obstruction; biliary stents